Attitude towards online shopping and its influence on purchase intentions: an urban Indian perspective. (19th June 2020) - Hebbar, Sunith; Kamath, Giridhar B.; Mathew, Asish Oommen; Kamath, Vasanth
Unprecedented growth in online shopping necessitates better understanding of the consumer behavioural patterns for effective decision making. This study focuses on identifying the factors that influence the attitude and purchase intention (PI) of online shoppers, specifically, in the context of urban millennials. The study identifies various factors related to the benefits and risks of online shopping which in turn influence the consumer attitude towards online shopping and hence, purchase intention. We propose a conceptual model based on the gaps identified in contemporary literature. Using structural equation modelling (SEM), we test the hypotheses developed in this study are tested. The results indicate that perceived benefits have a significant influence on attitude toward online shopping, and attitude and domain-specific innovativeness has a significant influence on purchase intention. Further system dynamics (SD) is used to simulate a case of an online food delivery student start-up. The findings of the hypothesis tests are validated.